Pengenalan dan Penerapan Pembangkit Listrik Tenaga Surya di Desa Muara Kilis Kabupaten Tebo Jambi - Yani Prabowo; Suwasti Broto; Gunawan P. Utama; Grace Gata; Yuliazmi Yuliazmi (University of Merdeka Malang, 2020)
Community service activities were carried out to introduce solar panel technology to the Suku Anak Dalam village community in Muara Kilis Jambi, where the village had some electricity that had not yet been electrified by PLN. Because PLN has not reached the electricity network, the general public uses generators with fuel as a motor for generating electricity. The use of fuel, especially in rural areas can be said to require expensive costs for operations coupled with the cost of engine maintenance. The use of solar panels is one of the easy and inexpensive alternatives to get electricity. The installation system that is applied is the DC system will make more economical and low-cost installation. With the implementation of this service, one month is enough to meet the electricity needs in the household for every night. The residents can do the installation well and can analyze the electricity needs to be used. In addition to installing the panels, they have understood the laying of the panels according to recommendations using the PV Power System software. How to cite:Prabowo, Y., Broto, S., Utama, G. P., Gata, G., Yuliazmi. (2020). Pengenalan dan Penerapan Pembangkit Listrik Tenaga Surya di Desa Muara Kilis Kabupaten Tebo Jambi. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 70-78.DOI: https://doi.org/10.26905/abdimas.v5i1.3555